SCREEN NOW: a new educational resource for diabetes and eye health. (2nd December 2021) - Phillips, Anne
Abstract : Diabetes retinopathy is a feared complication of diabetes. Anne Phillips describes a new educational resource to explain the need for retinal screening to people living with diabetes and health professionals